Study guide. V.1 : chapters 1-14 [for] Intermediate accounting - Weygandt, Jerry J.; Kieso, Donald E.; Kieso, Douglas W.; Warfield, Terry D. (New York ; Chichester : John Wiley & Sons, 2001)
Financial accounting and accounting standards. Conceptual framework underlying financial accounting. The accounting information system. Income statement and related information. Balance sheet and statement of cash flows. Accounting and the time value of money. Cash and receivables. Valuation of inventories: A cost basis approach. Inventories: additional valuation issues. Acquisition and disposition of property, plant, and equipment. Depreciation, Impairments, and Depletion. Intangible assets. Current liabilities and contingencies. Long-term liabilities.
Keywords: Accounting; Accounting -- Problems, exercises, etc